Latin American Foreign Policies - Lambert, Peter. author. aut Link
XI, 272 p.
Keywords: In recent years several Latin American countries have adopted a more assertive and autonomous stance in their foreign policy. The growing rejection of neo-liberalism as an ideological dogma seems to have given space to more pragmatic stances in favour of national interests.